In situ observations of Berkovich indentation induced phase transitions in crystalline silicon films. (15th July 2016) - Gerbig, Yvonne B.; Michaels, Chris A.; Cook, Robert F.
Abstract: The pressure induced phase transitions of crystalline Si films were studied in situ under a Berkovich probe using a Raman spectroscopy-enhanced instrumented indentation technique. The observations suggested strain and time as important parameters in the nucleation and growth of high-pressure phases and, in contrast to earlier reports, indicate that pressure release is not a precondition for transformation to high pressure phases. Graphical abstract: In-situ Raman mapping during loading segment of Berkovich indentations in silicon.